FORMULATION AND EVALUATION OF SOLID SELF-EMULSIFYING DRUG DELIVERY SYSTEM OF GLICLAZIDE - Deshmukh, Suwarna R.; Bakhle, Suparna S.; Upadhye, Kanchan P.; Dixit, Gouri R. (International Journal of Pharmacy and Pharmaceutical Sciences, 2016)
Objective: Gliclazide (GCZ) is a widely prescribed anti-diabetic drug belongs to class IÎ™ under BCS and exhibit low and variable oral bioavailability due to its poor aqueous solubility. The present investigations highlight the development of solid self-emulsifying drug delivery system (solid-SEDDS) for improved oral delivery of the poorly water-soluble drug, GCZ. Methods: Various oils, surfactant and co-surfactant, were screened for their emulsification ability. Ternary phase diagrams were plotted to identify the zone of micro-emulsification. Liquid SEDDS of the drug were formulated using lemon oil as the oil phase, tween 80, as the surfactant, and labrasol, as the co-surfactant. The optimized liquid SEDDS was transformed into free-flowing powder using florite R as the adsorbent. Results: Self-emulsifying powder retained the self-emulsifying property of the liquid SEDDS. The morphology of solid-SEDDS from scanning electron microscopy studies demonstrated the presence of spherical, granular particles indicating good flowing ability. X-ray powder diffraction studies confirmed solubilization of the drug in the lipid excipients and/or transformation of a crystalline form of the drug to amorphous form. In vitro dissolution studies revealed enhanced release of the drug from solid-SEDDS as compared to plain drug and marketed formulation. Conclusion: Thus it can be concluded that solid-SEDDS, amenable for the development of solid dosage form, can be successfully developed using florite R with the potential of enhancing the solubility, dissolution rate, and bioavailability of the drug.